UJI PENGGUNAAN KOMPOS KULIT BUAH KAKAO DAN PUPUK NPK TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) ASAL KECAMBAH KEMBAR PADA MEDIUM SUBSOIL ULTISOL - Dwiki Yuanda; Adiwirman Adiwirman; Ardian Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study the interaction KKBK with NPK and determined the best treatment for growing of twin sprouts oil palm seedlings (Elaeis guineensis Jacq.) in the subsoil ultisol medium. Research conducted at the Laboratory of Plant Experimental Farm, Faculty of Agriculture, University of Riau, Pekanbaru. The study was conducted four months from February to May 2016, carried out with completely randomized design (CRD) factorial comprises two factors and 3 replications. KKBK first factor (K) comprises 4 levels : K0 = without KKBK, K1 = KKBK 12.5 tonnes/ha or 50 g/plant, K2 = KKBK 25 tonnes/ha or 100 g/plant, K3 = 37.5 tonnes KKBK/ha or 150 g/plant. The second factor NPK (P) comprises 4 levels : P0 = ¼ dose of 0.1125 tonnes/ha or 6.25 g/plant, P1 = ½ dose of 0.225 tonnes/ha or 12.5 g/plant, P2 = ¾ doses of 0.3375 tonnes/ha or 18.75 g/plant, P3 = 1 dose of 0.45 tonnes/ha or 25 g/plant. Each unit contains 2 plant samples. The parameters those observed were plant height, leaf number, stump diameter, root volume, seedlings fresh weight ,seedling dry weight, fresh and dry weight of shoot and roots. Data were analyzed with analysis of variance and Honestly Significant Difference (HSD) of 5%. The results showed interaction of KKBK 150 g/plant and NPK 25 g/plant in the nursery generate the highest of all the parameters compared to other treatments. Keywords : Compost of Cocoa Fruit skin (KKBK), NPK Fertilizer, Oil Palm Seedlings, Ultisol Subsoil.